Omamori - McGill, Richard (Toronto Bantam Books, 1988)
A saga of three generations of two families--the American Napier clan and the Japanese Hosokawa family--and the silk dynasty that represents their shared fortune.
English Fiction.
Keywords: Silk industry -- Japan